The Design and Simulation of Steel Ball Whole Surface Unfolding Mechanism - ZHAO Yan-ling; WANG Qi-yu; BAO Yu-dong; XIANG Jing-zhong (Journal of Harbin University of Science and Technology)
In order to achieve fast and efficient of the steel ball surface defects of automatic on-line detection， On the basis of analyzing the basic working principle of the steel ball unfolding mechanism，the Unfolding mechanism are analyzed and designed，established the mathematical model of steel ball surface，to determine the relative and the important parameters between the expansion wheel，driving wheel and supporting wheels. The simulation analysis and experimental verification of the unfolding mechanism are carried out from the point of view of collision force. The results show that the unfolding mechanism to achieve the fully expanded on the surface of the steel ball and completed the rapid detection of steel ball，it provides a reliable basis for the prototype manufacture of steel ball detection device.